Analysis of Lactobacillus Products for Phages and Bacteriocins That Inhibit Vaginal Lactobacilli - Lin Tao; Sylvia I. Pavlova; Susan M. Mou; Wen-ge Ma; Ali O. Kiliç (Hindawi Limited, 1997)
Objective: Bacterial vaginosis is associated with an unexplained loss of vaginal lactobacilli. Previously, we have identified certain vaginal lactobacilli-released phages that can inhibit in vitro other vaginal lactobacilli. However, there is no apparent route for phages to be transmitted among women. The purpose of this study was to identify whether certain Lactobacillus products commonly used by women release phages or bacteriocins that can inhibit vaginal lactobacilli.